Ocular surface disease index in Graves’ orbitopathy: a cross-sectional study - Maglionico, Maria Novella; Lanzolla, Giulia; Figus, Michele; Cosentino, Giada; Comi, Simone; Marinò, Michele; Santini, Ferruccio; Posarelli, Chiara (Frontiers in Endocrinology, 2024)
Introduction Graves' Orbitopathy (GO) is an autoimmune disorder characterized by inflammation of orbital tissues, leading to various ocular manifestations, including ocular surface disease. This cross-sectional study aimed to assess the presence of ocular surface disease using the Ocular Surface Disease Index (OSDI) in patients with Graves' disease (GD) and moderate-to-severe active GO compared to those with GD and mild non-active GO. Additionally, we aimed to investigate the correlation between ocular surface disease and the eye features of GO. Methods Consecutive GD patients with GO referred to the Ophthalmology and Endocrinology Units of the University Hospital of Pisa between June 2022 and February 2023 were enrolled. OSDI scores were obtained from 79 GD patients, categorized into moderate-to-severe active GO and mild non-active GO groups. Results OSDI scores were significantly higher in patients with moderate-to-severe active GO compared to those with mild non-active GO (P=0.0006). A cutoff value of 33 for positive tests revealed a higher frequency of pathological OSDI in moderate-to-severe active GO patients compared to mild non-active GO patients (P=0.0221; OR 3.673, CI 1.277-9.531). Within the moderate-to-severe active GO group, a significant positive correlation was found between OSDI and Clinical Activity Score (CAS) (R= 0.3867, 95% CI from 0.1403 to 0.5880; P=0.0030). Using a cutoff value of 55 (the 75th percentile of the study population), patients with CAS ≥ 3 had a significantly higher proportion of pathological OSDI compared to those with CAS <3 (P=0.0039; OR 4.075, CI 1.619-10.39). Proptosis values ≥ 22 mm and the presence of lagophthalmos were identified as significant risk factors for ocular surface disease development (P=0.0406 and P=0.0493, respectively). Discussion Our study highlights a significantly higher prevalence of ocular surface disease, as measured by OSDI, in patients with moderate-to-severe active GO compared to those with mild non-active disease. The degree of GO activity positively correlates with ocular surface involvement, and proptosis and lagophthalmos increase the risk of its occurrence. These findings emphasise the importance of assessing and managing ocular surface health in GO patients. Early identification and appropriate treatment of ocular surface disease need to be pursued to improve patient management.